IDENTIFIKASI FUNGI YANG BERKEMBANG PADA BATANG SAWIT (Elaeis guineensis Jacq.) Pasca Penebangan (Identification of fungi that developed in post-harvest oil palm trunk (Elaeis guineensis Jacq.)) - Hisar panjaitan; Ridwanti Batubara; Yunasfi Yunasfi (Peronema Forestry Science Journal, 2013)
The research aims to know the kinds of fungi that grow on palm trunk after logging in the process of rejuvnation of palm. The research was conducted in Kebun Percobaan Tambunan A Universitas Sumatra Utara. Fungi isolated and identified in Microbiology Laboratory of the Department of Biology Faculty of Mathematics and Natural Sciences, University of North Sumatra. The research was conducted from September 2011 until November 2011. The results obtained, four types of fungi found on oil palm trunks that have been process of rejuvnation, wich is taken from four palm  as a sample. for each palm trunk, made ​​a division at the base of the trunk, middle, and end of the trunk. From the results of isolation obtained the Arthrinium phaespermum, Chaetomium brasiliense, Penicillium simplicissimum and Ulocladium botrytis as a result of identification from the sample. The type of fungi that most identified from the palm trunk is a type of fungi Arthrinium phaeospermumKey words : Elaeis guineensis Jacq, Fungi, Palm trunks